Knautia arvensis (Caprifoliaceae), a new record for the flora of Turkey - Tunçkol, Bilge; Aksoy, Necmi; Yaşayacak, Hasan; Tunçkol, Bilge (Magyar Biologiai Tarsasag (Hungarian Biological Society), 2021)
Knautia arvensis (L.) Coult. (Caprifoliaceae), collected from Küre Mountains National Park (Kastamonu Section), is reported for the first time for the flora of Turkey. A brief description of the plant along with photographs and distribution map is given. Additionally, its taxonomic relationship with other closely allied taxa are examined and discussed. An identification key to the species of genus Knautia in Turkey is provided. © 2021 Elsevier B.V., All rights reserved.
Keywords: Dipsacoideae; Field Scabious; Identification Key; New Floristic Record; Northern Turkey